Healing Threads of Care: Weaving Resilience in Mothers of Preterm Infants - Abisha Mary Antony Johnson Kennady; Shankar Shanmugam Rajendran; Kannan Kasinathan; Grace Anita Samuel; Ashalin Raja Brintha Palas; Shanmugapriya Shanmugasundharam; Dr. Winston Thomas (The Bioscan, 2025)
The mothers with pre-term infant have more bio-psychosocial activity thus facing challenges in take care of their pre-term infant. This study assessed Bio-psychosocial needs and to explore the solicitude experience among 50 adolescents at a tertiary care hospital using a mixed-method study by quantitative convenient sampling technique and by qualitative purposive sampling technique. Data were collected through socio-demographic details, the parent stress scale, Edinburgh Postnatal Depression Scale, multidimensional scale of perceived social support Scale. Results showed that in Pre-test findings 58% experienced moderate stress, 42% severe stress,84% had borderline depression, 16% clinical depression, 74% reported low perceived social support. Post-test findings 64% experienced mild stress, 36% moderate stress, 76% had normal depression scores, 24% borderline depression, 62% reported moderate social support, 38% high support. Paired t-test showed significant improvement in stress (t=15.32, p<0.001), depression (t=18.76, p<0.001), and perceived social support scores (t=20.14, p<0.001) after the intervention. The study findings demonstrate the significant impact of a tailor-made intervention on improving the bio-psychosocial needs of mothers with pre-term infants. The intervention led to substantial reductions in stress and depression levels while enhancing perceived social support. The importance of healthcare professional support and peer connections aligns with findings.